Specific lectin binding sites during in vitro capacitation and acrosome reaction in boar spermatozoa. Issue 1 (1st January 2021) - Robles-Gómez, Laura; González-Brusi, Leopoldo; Sáez-Espinosa, Paula; Huerta-Retamal, Natalia; Cots-Rodríguez, Paula; Avilés, Manuel; Gómez-Torres, María José
Abstract: Sperm glycocalyx and plasma membrane undergo outstanding modifications during fertilization. However, it is unclear how in vitro capacitation time and acrosome reaction affect the specific location of boar sperm glycoconjugates. This study aimed to identify lectin binding patterns and to describe the sequential changes during different in vitro capacitation times (1 and 4 h) and acrosome reaction in boar spermatozoa. With Aleuria aurantia agglutinin (AAA), most uncapacitated cells were labelled in the postacrosomal region. Nevertheless, after 1 h of in vitro capacitation and the acrosome reaction, most AAA binding sites were in the acrosomal region. With Concanavalin A (ConA), most sperm were labeled in the postacrosomal region before and after capacitation. After the acrosome reaction induction, this pattern changed to a highly stained acrosomal and postacrosomal regions. Peanut agglutinin (PNA) binding sites were in the acrosomal region in uncapacitated and capacitated sperm. In acrosome reacted sperm after 4h capacitation, the most frequent pattern showed remaining positive labeling in the central area of the head. With Pisum sativum agglutinin (PSA), most uncapacitated cells showed a postacrosomal region staining. Nevertheless, faint stained all over the head and highly acrosomal region labelling was observed in the major part of capacitated and acrosome reacted sperm respectively. With Wheat germ agglutinin (WGA), the most representative pattern in uncapacitated, capacitated and acrosome reacted sperm was labelled in the acrosomal region. Regarding capacitation time, the most significant changes in the most representative pattern were observed in acrosome reacted spermatozoa after 4 h of in vitro capacitation. Highlights: Lectins allow detailed descriptions of eight different populations in boar sperm. Changes in lectin binding patterns during capacitation are time dependent. Lectin binding patterns significantly change after 4 h of in vitro capacitation.